USE OF DRONES FOR DELIVERY OF MEDICINE AND BLOOD IN REMOTE AREAS - Loso Judijanto; Syafril Barus; Arnes Yuli Vandika (CV. ADIBA AISHA AMIRA, 2025)
The use of drone technology for the delivery of medicines and blood in remote areas has emerged as an innovative solution to some of the logistical challenges in healthcare. The study aims to evaluate the effectiveness, viability, and impact of the use of drones in improving access to essential medicines and blood supplies in hard-to-reach locations. Research methods carried out through the study of literature. Research results show that drones can not only significantly reduce delivery times and ensure reliability in delivering medical aid, but also offer a cost-effective solution compared to traditional transport methods. The study underscores the importance of a multidisciplinary approach in addressing barriers to delivery of health services in remote areas and exploring the future of drones as a major tool in medical follow-up response and health logistics delivery.